Preparation method of oxide dispersion strengthened austenitic stainless steel and nuclear fuel cladding material application

By adding Zr and Y2O3 to oxide dispersion strengthened austenitic stainless steel, a refined Zr-YO dispersion phase and an Al2O3 protective oxide film are formed, which solves the problems of corrosion resistance and radiation swelling in oxide dispersion strengthened steel in supercritical water/supercritical carbon dioxide cooled nuclear reactors, and achieves excellent corrosion resistance and radiation resistance.

CN120738564BActive Publication Date: 2026-11-06SHANGHAI JIAOTONG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510652821.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2026-11-06
Estimated Expiration
2045-05-21

AI Technical Summary

Technical Problem

Existing oxide dispersion reinforced steels have poor corrosion resistance in supercritical water/supercritical carbon dioxide cooled nuclear reactors, and traditional austenitic stainless steels are prone to irradiation swelling failure, making it difficult to meet the service requirements of cladding materials.

Method used

By adding Zr and Y2O3, a refined Zr-YO dispersed phase and an Al2O3 protective oxide film are formed. Combined with hot isostatic pressing and heat treatment processes, oxide dispersion strengthened austenitic stainless steel is prepared, which improves the corrosion resistance and radiation resistance of the material.

Benefits of technology

A continuous Al2O3 oxide film is generated in a supercritical water and supercritical carbon dioxide environment. The dispersed phase captures irradiation defects, which significantly improves the corrosion resistance and radiation swelling resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120738564B_ABST
    Figure CN120738564B_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing oxide dispersion-strengthened austenitic stainless steel and its application as a nuclear fuel cladding material. The material comprises Cr, Ni, Al, Mo, Nb, Zr, Y₂O₃, and C, with the balance being Fe. By mass fraction, Cr is 20.0–22.0 wt.%; Ni is 28.0–30.0 wt.%; Al is 2.0–3.0 wt.%; Mo is 1.0–2.0 wt.%; Nb is 0.6–1.0 wt.%; Zr is 0.1–0.4 wt.%; Y₂O₃ is 0.05–0.15 wt.%; C is 0.06–0.1 wt.%; and the balance is Fe. This material can form a continuous protective oxide film of Al₂O₃ in supercritical water and supercritical carbon dioxide. The interface formed by the dispersed micro / nano precipitates and the matrix can absorb radiation defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alloys, specifically relating to a method for preparing oxide dispersion strengthened austenitic stainless steel and its application as a nuclear fuel cladding material. Background Technology

[0002] Supercritical water-cooled nuclear reactors and supercritical carbon dioxide-cooled nuclear reactors are important candidates for next-generation nuclear reactors, which can improve reactor efficiency to ~45% and have significant economic advantages. Cladding material is the material that contains nuclear fuel in a nuclear reactor; it is the first safety barrier and one of the most critical materials in a nuclear reactor.

[0003] A common characteristic of supercritical water / supercritical carbon dioxide cooled nuclear reactors is their high operating temperature (reactor outlet temperature ≥500℃). Both high-temperature supercritical water and supercritical carbon dioxide possess extremely strong corrosive properties, posing a severe challenge to the corrosion resistance of the cladding materials. Furthermore, the cladding materials of supercritical water / supercritical carbon dioxide cooled nuclear reactors are also subjected to the most severe neutron radiation exposure in the reactor. Therefore, developing novel corrosion-resistant and radiation-resistant cladding materials is a crucial prerequisite for ensuring the successful design and construction of supercritical water / supercritical carbon dioxide cooled nuclear reactors.

[0004] Traditional zirconium alloy cladding materials are completely inadequate to meet the requirements of the intense radiation and highly corrosive environment faced by supercritical water / supercritical carbon dioxide cooled nuclear reactor cladding materials. In recent years, oxide dispersion strengthened (ODS) steel has become an important candidate for next-generation nuclear reactor cladding materials due to its excellent radiation resistance. However, the matrix of current ODS steels is mostly iron oxide steel (Cr mass fraction of 9%-12%), which has poor corrosion resistance in supercritical water / supercritical carbon dioxide, making it difficult to meet the requirements. Austenitic stainless steel has better corrosion resistance; however, traditional commercial austenitic stainless steels, such as 316LN and 304L stainless steel, corrode rapidly in supercritical water / supercritical carbon dioxide, making it difficult to meet the high corrosion requirements of supercritical water / supercritical carbon dioxide cooled nuclear reactor cladding materials. In recent years, novel aluminum-containing austenitic stainless steels have become an important development direction for cladding materials of supercritical water / supercritical carbon dioxide cooled nuclear reactors because they can form a protective Al2O3 oxide film in supercritical water and supercritical carbon dioxide. However, austenitic stainless steels are prone to radiation swelling failure, which has become a key obstacle restricting their application. Therefore, combining the radiation resistance of oxide dispersion strengthened steels with the corrosion resistance of aluminum-containing austenitic stainless steels, the development of oxide dispersion strengthened aluminum-containing austenitic stainless steels has become an important development direction for the design and manufacture of cladding materials for supercritical water / supercritical carbon dioxide cooled nuclear reactors.

[0005] However, Al reacts with Y₂O₃ at high temperatures to form coarse Al-YO phases, significantly reducing the number density of oxides and thus lowering the material's radiation resistance and mechanical properties. Studies have shown that the oxide formation energy of Zr is lower than that of metallic Al, and the diffusion coefficient of Zr metal in the Fe matrix is ​​smaller than that of Al. Therefore, research on adding Zr to slow down the nucleation and aggregation rate of metal oxides, thereby refining oxide particles and forming Zr-YO instead of coarse Al-YO, has become an important technical approach. Therefore, through reasonable technological innovation, supporting the design and preparation of novel aluminum-containing austenitic stainless steels with oxide dispersion strengthening, it is possible to develop corrosion-resistant and radiation-resistant materials that meet the requirements of cladding materials for supercritical water / supercritical carbon dioxide cooled nuclear reactors. Summary of the Invention

[0006] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0007] In view of the problems existing in the above and / or prior art, the present invention is proposed.

[0008] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide an oxide dispersion strengthened austenitic stainless steel.

[0009] To solve the above-mentioned technical problems, the present invention provides the following technical solution: an oxide dispersion strengthened austenitic stainless steel, characterized in that it contains the elements Cr, Ni, Al, Mo, Nb, Zr, Y2O3, C and Fe;

[0010] The composition, calculated by mass fraction of raw materials, includes 20.0–22.0 wt.% of Cr, 28.0–30.0 wt.% of Ni, 2.0–3.0 wt.% of Al, 1.0–2.0 wt.% of Mo, 0.6–1.0 wt.% of Nb, 0.1–0.4 wt.% of Zr, 0.05–0.15 wt.% of Y₂O₃, and 0.06–0.1 wt.% of C, with the balance being Fe.

[0011] As a preferred embodiment of the oxide dispersion strengthened austenitic stainless steel of the present invention, wherein: the oxide dispersion strengthened austenitic stainless steel, calculated by mass fraction, has the following composition: Cr 21.0 wt.%; Ni 29.0 wt.%; Al 2.5 wt.%; Mo 1.5 wt.%; Nb 0.6 wt.%; Zr 0.2 wt.%; Y₂O₃ 0.08 wt.%; C 0.08 wt.%; with the balance being Fe.

[0012] As a preferred embodiment of the oxide dispersion strengthened austenitic stainless steel of the present invention, it further possesses the following characteristics:

[0013] (i) After 2000 hours of corrosion in supercritical water at 550℃ / 25MPa, the weight gain was 14.26–14.72 mg·dm2;

[0014] (ii) After 2000 hours of corrosion in supercritical carbon dioxide at 550℃ / 25MPa, the weight gain was 5.45–5.53 mg·dm2;

[0015] (iii) The swelling rate of Fe ion irradiation at 550℃ for 50 dpa was 0.31–0.34%;

[0016] (iiii) The elongation at 550℃ is 35.2% to 36.4%.

[0017] Another objective of this invention is to overcome the shortcomings of the prior art and provide a method for preparing oxide dispersion strengthened austenitic stainless steel, characterized by comprising:

[0018] Fe, Cr, Ni, Nb, Mo and C are mixed and then smelted under vacuum and electricity. After the steel is liquefied and cleaned, Al and Zr are added and refined under vacuum conditions. Then, the mixture is cast, forged, heat treated and sprayed with gas atomized powder to obtain master alloy powder.

[0019] Zr powder and Y2O3 powder were ball-milled under a high-purity argon atmosphere to obtain Zr-YO powder;

[0020] The master alloy powder and Zr-YO powder were ball-milled and mixed under a high-purity argon atmosphere to obtain a mixed powder.

[0021] The mixed powder is hot isostatically pressed and solidified, then forged and heat-treated to obtain the compound dispersion strengthened austenitic stainless steel.

[0022] In a preferred embodiment of the preparation method described in this invention, the refining temperature is 1470–1530°C and the time is 8–12 min.

[0023] As a preferred embodiment of the preparation method described in this invention, the Zr powder and Y2O3 powder are ball-milled under a high-purity argon atmosphere to obtain Zr-YO powder, wherein the mass ratio of Zr to Y elements is not less than 1.03, and the total mass of Zr powder and Y2O3 powder is not less than 100g; the mass fraction of anhydrous ethanol added during ball milling is 2.5% of the total powder mass; the ball-to-powder ratio is 5-10:1, the ball milling time is 25-50h, and the rotation speed is 200-400r / min.

[0024] As a preferred embodiment of the preparation method described in this invention, the master alloy powder and Zr-YO powder are ball-milled and mixed under a high-purity argon atmosphere to obtain a mixed powder, wherein the total content of Y2O3 is not more than 0.15% by controlling the mass of Zr-YO powder obtained; the mass fraction of anhydrous ethanol added during ball milling is 2.5% of the total mass of the powder; the ball-to-powder ratio is 6-12:1; the ball milling time is 50-150 h, and the rotation speed is 150-300 r / min.

[0025] As a preferred embodiment of the preparation method described in this invention, the mixed powder is hot isostatically pressed and solidified before forging, wherein the forging conditions are an initial forging temperature of 1100-1200℃, a final forging temperature of not less than 950℃, and a total forging ratio of not less than 4:1.

[0026] As a preferred embodiment of the preparation method described in this invention, the heat treatment includes solution treatment and aging, wherein the solution treatment temperature is 1100-1200℃ and the holding time is 1-2h; the aging temperature is 550-650℃ and the holding time is 100-200h.

[0027] Another objective of this invention is to overcome the shortcomings of the prior art and provide an application of oxide dispersion strengthened austenitic stainless steel in the cladding material of supercritical water / supercritical carbon dioxide cooled nuclear reactors.

[0028] Beneficial effects of this invention:

[0029] This invention provides a method for preparing oxide dispersion-strengthened austenitic stainless steel and its application as a nuclear fuel cladding material. This material can generate a continuous protective oxide film of Al2O3 in supercritical water and supercritical carbon dioxide, exhibiting excellent corrosion resistance. Simultaneously, the interface formed between the dispersed micro / nano precipitates (such as Zr-YO and Ni3Al precipitates) and the matrix can absorb irradiation defects, ensuring excellent resistance to radiation swelling. Attached Figure Description

[0030] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:

[0031] Figure 1 This is a morphology diagram of the dispersed oxides in the novel austenitic stainless steel material with oxide dispersion strengthening obtained in Example 1 of the present invention.

[0032] Figure 2 This is a morphology diagram of the oxide film after corrosion in supercritical water at 550℃ for 1000 hours in Example 1 of the present invention.

[0033] Figure 3 This is a morphology diagram of the oxide film after corrosion in supercritical carbon dioxide at 550℃ for 1000 hours in Example 1 of the present invention.

[0034] Figure 4 The irradiated cavity image was obtained by irradiating the cavity with 5 MeV iron ions at 550°C in Example 1 of the present invention.

[0035] Figure 5 This is a schematic diagram of the dynamic circulating supercritical water corrosion system used in the testing of this invention.

[0036] Figure 6 This is a schematic diagram of the dynamic cyclic supercritical carbon dioxide corrosion system used in the testing of this invention. Detailed Implementation

[0037] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0038] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0040] Unless otherwise specified, all raw materials used in the embodiments of this invention are commercially available. See Table 1 for details.

[0041] Table 1

[0042] name Retail channels High-purity nickel powder Direct supply from universities and research institutions of China Metallurgical Research Institute High-purity iron powder Direct supply from universities and research institutions of China Metallurgical Research Institute High-purity molybdenum powder Direct supply from universities and research institutions of China Metallurgical Research Institute High-purity chromium powder Direct supply from universities and research institutions of China Metallurgical Research Institute High-purity niobium powder Direct supply from universities and research institutions of China Metallurgical Research Institute High-purity graphite powder Direct supply from universities and research institutions of China Metallurgical Research Institute High-purity aluminum granules Direct supply from universities and research institutions of China Metallurgical Research Institute High-purity zirconium particles Zhongke Yannuo High-purity yttrium trioxide powder Zhongke Yannuo

[0043] Example 1

[0044] This embodiment provides a method for preparing oxide dispersion-strengthened austenitic stainless steel for use as cladding material in supercritical water / supercritical carbon dioxide cooled nuclear reactors:

[0045] The raw material composition by mass percentage is as follows: Cr: 21.0 wt.%; Ni: 29.0 wt.%; Al: 2.5 wt.%; Mo: 1.5 wt.%; Nb: 0.6 wt.%; Zr: 0.2 wt.%; Y2O3: 0.08 wt.%; C: 0.08 wt.%; balance Fe.

[0046] (1) Pure metal raw materials Fe (45.04 wt.%), Cr (21.0 wt.%), Ni (29.0 wt.%), Nb (0.6 wt.%), Mo (1.5 wt.%), and C (0.08 wt.%) were mixed in a vacuum induction furnace and placed in a crucible for vacuum melting. (Melting temperature was 1500℃, and vacuum degree was 1 Pa.) During melting, the efficiency of carbon deoxidation, nitrogen, phosphorus and sulfur was enhanced by relying on the high vacuum environment and low melting rate. After the steel was liquefied and cleaned, the balance Al (2.5 wt.%) and Zr (0.1 wt.%) were added. After full melting, the mixture was refined at 1500℃ for 10 minutes. At the same time, when the alloy liquid was kept at 1500℃, argon gas at 0.015 MPa was injected to reduce the content of impurities O, N, P and S in the material.

[0047] (2) The above solution was poured into ingots at a pouring temperature of 1450℃, and then demolded to obtain a cast billet; then forging was carried out with the following parameters: initial forging temperature of 1200℃, final forging temperature of 950℃, and forging ratio of 5:1; air cooling was performed to obtain a stainless steel forged billet round bar (20mm in diameter). Afterwards, the forging material was heat treated with the following parameters: solution treatment at 1000℃ for 12 hours to ensure the uniformity of the material microstructure; the oxide film on the surface of the solution-treated material was peeled off and pickled to obtain a master alloy round bar.

[0048] (3) The above-mentioned master alloy round bar is sprayed with gas atomization powder, the atomization gas pressure is controlled at 5MPa, the superheat is 200℃, and the protective atmosphere is argon gas with a purity of not less than 99.999%. The final particle size of the master alloy powder is between 45-75μm.

[0049] (4) Weigh Zr powder and Y2O3 powder and ball mill them, with a Zr powder to Y2O3 powder mass ratio of 1.25 (weighed according to the ratio of Zr: 0.1wt.% and Y2O3: 0.08wt.% in the total material content, and the total mass of Zr powder and Y2O3 powder to be ball-milled is 180g); add anhydrous ethanol as a process control agent during ball milling. Its mass fraction is 2.5% of the total powder mass; use argon gas with a purity of 99.9% during ball milling; the ball-to-material ratio is 8:1; the ball milling time is 50h, the rotation speed is 200r / min, and Zr-YO powder particles are obtained.

[0050] (5) Weigh the master alloy powder and Zr-YO powder particles at a mass ratio of 99.82:0.18, and then mix the two powders thoroughly. The mixing method is as follows: the mixing atmosphere is argon gas with a purity of 99.999% or higher; the mixing speed is 20 r / min; and the mixing time is 10 h.

[0051] (6) The above-mentioned uniformly mixed powder is then ball-milled. The ball milling parameters are controlled as follows: the ball milling protective atmosphere is argon gas with a purity of 99.999% or higher; the ball-to-material ratio is 8:1; the ball milling time is 100h; and the rotation speed is 200r / min.

[0052] (7) The mixed powder obtained in step (6) is pressed into shape using hot isostatic pressing. The process is as follows: pressing stress 150 MPa, temperature 1100℃, time 5 h. The formed stainless steel is then forged, with an initial forging temperature of 1100℃, a final forging temperature of 950℃, and a total forging ratio of 5:1 to obtain forged material.

[0053] (8) The profile is subjected to a two-step heat treatment of solution and aging, as follows: the solution temperature is 1100℃ and the holding time is 1h; the aging temperature is 600℃ and the holding time is 200h.

[0054] Example 2

[0055] The raw material composition by mass percentage is as follows: Cr: 21.5 wt.%; Ni: 30.0 wt.%; Al: 2.5 wt.%; Mo: 2.0 wt.%; Nb: 0.6 wt.%; Zr: 0.2 wt.%; Y2O3: 0.08 wt.%; C: 0.08 wt.%; balance Fe.

[0056] (1) Pure metal raw materials Fe (43.04 wt.%), Cr (21.5 wt.%), Ni (30.0 wt.%), Nb (0.6 wt.%), Mo (2.0 wt.%), and C (0.08 wt.%) were mixed in a vacuum induction furnace and placed in a crucible for vacuum melting. During melting, the high vacuum environment and low melting rate enhanced the efficiency of carbon deoxidation, nitrogen, phosphorus, and sulfur removal. After the steel was liquefied and cleaned, the remaining Al (2.5 wt.%) and Zr (0.1 wt.%) were added. After complete melting, the mixture was refined at a temperature of 1520°C for 15 minutes. At the same time, while the alloy liquid was kept at 1520°C, argon gas at 0.015 MPa was introduced to reduce the content of impurities O, N, P, and S in the material.

[0057] (2) The above solution was poured into ingots at a pouring temperature of 1450℃, and then demolded to obtain a cast billet; then forging was carried out with the following parameters: initial forging temperature of 1200℃, final forging temperature of 950℃, and forging ratio of 5:1; air cooling was performed to obtain a stainless steel forged billet round bar (20mm in diameter). Afterwards, the forging material was heat treated with the following parameters: solution treatment at 1050℃ for 12 hours to ensure the uniformity of the material microstructure; the oxide film on the surface of the solution-treated material was peeled off and pickled to obtain a master alloy round bar;

[0058] (3) Then, the above-mentioned master alloy round bar is sprayed with gas atomization powder, the atomization gas pressure is controlled at 5MPa, the superheat is 200℃, and the protective atmosphere is argon gas with a purity of not less than 99.999%. Finally, the particle size of the master alloy powder is between 45-75μm.

[0059] (4) Weigh Zr powder and Y2O3 powder and ball mill them, wherein the mass ratio of Zr powder to Y2O3 powder is 1.25 (weighed according to the ratio of Zr: 0.1wt.% and Y2O3: 0.08wt.% in the total content of the material, and the total mass of Zr powder and Y2O3 powder to be ball milled is 180g); add anhydrous ethanol as a process control agent during ball milling, the mass fraction of which is 2.5% of the total mass of the powder; use argon gas with a purity of 99.9% during ball milling; the ball-to-material ratio is 8:1; the ball milling time is 50h and the rotation speed is 200r / min to obtain Zr-YO powder particles;

[0060] (5) Weigh the master alloy powder and Zr-YO powder particles at a mass ratio of 99.72:0.28, and then mix the two powders thoroughly. The mixing method is as follows: the mixing atmosphere is argon gas with a purity of 99.999% or higher; the mixing speed is 20 r / min; and the mixing time is 10 h.

[0061] (6) The above-mentioned uniformly mixed powder is then ball-milled. Anhydrous ethanol, a process control agent, is added during ball milling. Its mass fraction is 2.5% of the total mass of the powder. The ball milling parameters are controlled as follows: the ball milling protective atmosphere is argon gas with a purity of 99.999% or higher; the ball-to-material ratio is 8:1; the ball milling time is 100h; and the rotation speed is 200r / min.

[0062] (7) The mixed powder obtained in step (6) is pressed into shape using hot isostatic pressing. The process is as follows: pressing stress 150 MPa, temperature 1100℃, time 5 h. The formed stainless steel is then forged, with an initial forging temperature of 1100℃, a final forging temperature of 950℃, and a total forging ratio of 5:1 to obtain forged material.

[0063] (8) The profile is subjected to a two-step heat treatment of solution and aging, as follows: the solution temperature is 1100℃ and the holding time is 1h; the aging temperature is 600℃ and the holding time is 200h.

[0064] Comparative Example 1

[0065] The difference from Example 1 is that, by mass percentage, Cr: 25.0 wt.%; Ni: 29.0 wt.%; Al: 2.5 wt.%; Mo: 1.5 wt.%; Nb: 0.6 wt.%; Zr: 0.2 wt.%; Y2O3: 0.08 wt.%; C: 0.08 wt.%; with the balance being Fe.

[0066] Comparative Example 2

[0067] The difference from Example 1 is that, by mass percentage, Cr: 21.0 wt.%; Ni: 25.0 wt.%; Al: 2.5 wt.%; Mo: 1.5 wt.%; Nb: 0.6 wt.%; Zr: 0.2 wt.%; Y2O3: 0.08 wt.%; C: 0.08 wt.%; with the balance being Fe.

[0068] Comparative Example 3

[0069] The difference from Example 1 is that, by mass percentage, Cr: 21.0 wt.%; Ni: 29.0 wt.%; Al: 4.5 wt.%; Mo: 1.5 wt.%; Nb: 0.6 wt.%; Zr: 0.2 wt.%; Y2O3: 0.08 wt.%; C: 0.08 wt.%; with the balance being Fe.

[0070] Comparative Example 4

[0071] The difference from Example 1 is that, by mass percentage, Cr: 21.0 wt.%; Ni: 29.0 wt.%; Al: 2.5 wt.%; Mo: 1.5 wt.%; Nb: 1.2 wt.%; Zr: 0.2 wt.%; Y2O3: 0.08 wt.%; C: 0.08 wt.%; with the balance being Fe.

[0072] Comparative Example 5

[0073] The difference from Example 1 is that, by mass percentage, Cr: 21.0 wt.%; Ni: 29.0 wt.%; Al: 2.5 wt.%; Mo: 1.5 wt.%; Nb: 0.6 wt.%; Y2O3: 0.08 wt.%; C: 0.08 wt.%; with the balance being Fe.

[0074] Comparative Example 6

[0075] The difference from Example 1 is that, by mass percentage, Cr: 21.0 wt.%; Ni: 29.0 wt.%; Al: 2.5 wt.%; Mo: 1.5 wt.%; Nb: 0.6 wt.%; Zr: 0.2 wt.%; C: 0.08 wt.%; with the balance being Fe.

[0076] Comparative Example 7

[0077] The difference from Example 1 is that the ball milling time of the mixed powder in step (6) is 25 hours.

[0078] Comparative Example 8

[0079] The difference from Example 1 is that the final forging temperature in step (7) is 750°C.

[0080] Comparative Example 9

[0081] The difference from Example 1 is that the solution temperature in step (8) is 1250°C and the aging temperature is 700°C.

[0082] The stainless steels obtained in the examples and comparative examples were subjected to uniform corrosion tests in supercritical water at 550℃ / 25MPa and supercritical carbon dioxide at 550℃ / 25MPa, tensile tests in air at 550℃, and Fe ion irradiation tests at 550℃. For the supercritical water uniform corrosion test and the high-temperature tensile test, the testing equipment used was a dynamic circulating supercritical water corrosion system designed by the research group; for the supercritical carbon dioxide uniform corrosion test, the testing equipment used was a dynamic circulating supercritical carbon dioxide corrosion system designed by the research group. A schematic diagram of the testing equipment system is shown below. Figure 5 , 6As shown. The Fe ion irradiation experiment was conducted using the 320kV high-charge-state ion integrated R&D platform of the Lanzhou Institute of Modern Physics. This platform is an open national experimental platform that can provide ions of more than 30 elements, including H, He, Bi, Fe, Si, Xe, Kr, Au, Ti, and U. The accelerating voltage is continuously adjustable in the range of ion energy from 5keV to 10MeV.

[0083] Two uniform corrosion tests were conducted using suspended specimens. The test standards referenced were: (1) ASTM E399 Standard Guide for Corrosion Tests in High Temperature or High Pressure Environment; (2) ASTM G111-97 (2013) Standard Guide for Corrosion Tests in High Temperature or High Pressure Environment; (3) GB / T19291-2003 General Principles for Corrosion Testing of Metals and Alloys; and (4) JB / T7901-2023 Laboratory Method for Uniform Corrosion Full Immersion Test of Metallic Materials. The weighed, progressively polished samples were suspended in an autoclave using nickel-chromium alloy wire. After 2000 hours of corrosion in a supercritical water / supercritical carbon dioxide environment at 550℃ / 25MPa, the samples were weighed to obtain the weight gain data.

[0084] The high-temperature tensile test uses sheet-like tensile specimens, and the test standard refers to GB / T 228.2-2015 Metallic Materials - Tensile Testing (Part 2: High-Temperature Test Method). The specimen is fixed to the tensile rod using clamps, and then the installation mode is activated to prevent any stress that may be introduced into the specimen during the autoclave closure process. The autoclave is then closed and the sealing bolts are tightened. After heating to the target temperature of 550℃, the inlet and outlet valves are opened to ensure that the pressure inside the autoclave is consistent with the ambient pressure. The specimen size parameters are entered into the tensile testing software, and the tensile rate is set to 10. -4 Click "Start Test" after / s. Maintain a stretching rate of 10. -4 / s, until it breaks. The system will automatically record the data.

[0085] The ion irradiation experiment used 5 MeV Fe ions to irradiate the material at a temperature of 550 degrees Celsius. SRIM calculations, combined with equipment current control, yielded a peak irradiation dose of 50 dPa for the sample. The irradiated sample was a 5×5×2 mm sample. 3 The sheet-like samples were polished to a mirror-like smoothness. During the experiment, the temperature and vacuum level of the irradiated samples were monitored to prevent surface oxidation caused by excessively high temperatures and oxidizing gas impurities.

[0086] The results are shown in Table 2.

[0087] Table 2

[0088]

[0089] As shown in Table 2, the tests indicate that, compared to Example 1, while increasing the Cr content in Comparative Example 1 improved the material's corrosion resistance in supercritical water and supercritical carbon dioxide environments, the excessively high Cr content caused brittleness, leading to a significant decrease in the material's radiation resistance and mechanical properties. In Comparative Example 2, decreasing the Ni content resulted in the precipitation and growth of the Sigma phase, along with coarsening of the Laves phase and a reduction in the reinforcing phase Ni3Al, thus decreasing the material's mechanical properties and radiation resistance. In Comparative Example 3, the excessively high Al content enhanced oxide film formation, which significantly improved the material's corrosion resistance, but also led to uneven oxide distribution. Furthermore, the high Al content caused it to react with Y2O3 to form coarse oxides, weakening radiation resistance and mechanical properties. In Comparative Example 4, the high Nb content resulted in uneven distribution of the reinforcing phase and reduced... The mechanical properties of the materials were affected; Comparative Example 5, without the addition of Zr, resulted in poor dispersion strengthening, the appearance of coarse Al-YO phases, and the lack of Zr reduced the material's ability to capture irradiation defects; Comparative Example 6, without the addition of Y2O3, prevented the formation of the dispersion strengthening phase Zr-YO, resulting in a decrease in resistance to corrosion by supercritical water and supercritical carbon dioxide, and a severe decrease in radiation resistance; Comparative Example 7, insufficient ball milling time led to insufficient and uneven distribution of the dispersion strengthening phase, reducing the material's radiation resistance; Comparative Example 8, cracking during forging caused material preparation failure, and the excessively low final forging temperature prevented the material from maintaining plastic deformation, ultimately leading to cracking; Comparative Example 9, excessively high solution temperature and aging temperature resulted in coarse grains and precipitates, which reduced the material's corrosion resistance, and the high-temperature elongation of the material was significantly lower than that of the examples.

[0090] Figure 1 This is a morphology diagram of the dispersed oxides in the novel austenitic stainless steel material obtained in Example 1 of the present invention. It can be seen that the particles are uniform in size and dispersedly distributed in the matrix, with an average particle size of less than 20 nm, which helps to suppress irradiation swelling and strengthen the matrix properties. Figure 2 , Figure 3 The images show the oxide film morphology after corrosion in supercritical water at 550℃ and supercritical carbon dioxide for 1000 hours, respectively, according to Example 1 of the present invention. The oxide film thickness is approximately 600 nm in the supercritical water environment and approximately 400 nm in the supercritical carbon dioxide environment, and a continuous Al2O3 oxide film is formed in both environments. This indicates that the present invention has good corrosion resistance in both corrosive environments, and a uniformly dispersed reinforcing phase can be observed. Figure 4The image shows irradiated voids obtained after irradiation with 5 MeV iron ions at 550°C in Example 1 of this invention. It can be seen that the material in Example 1 formed very few irradiated voids after 5 MeV iron ion irradiation, and the void diameter was less than 5 nm. This demonstrates the effectiveness of the dispersed strengthening phase, which can capture irradiated point defects and inhibit void growth.

[0091] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.

Claims

1. A method of producing an oxide dispersion strengthened austenitic stainless steel, characterized by: include, Fe, Cr, Ni, Nb, Mo and C are mixed and then smelted under vacuum and electricity. After the steel is liquefied and cleaned, Al and Zr are added and refined under vacuum conditions. Then, the mixture is cast, forged, heat treated and sprayed with gas atomized powder to obtain master alloy powder. Zr powder and Y2O3 powder were ball-milled under a high-purity argon atmosphere for 50-150 h to obtain Zr-YO powder. The master alloy powder and Zr-YO powder were ball-milled and mixed under a high-purity argon atmosphere to obtain a mixed powder. The mixed powder is hot isostatically pressed and solidified into a mold, then forged and heat-treated to obtain the compound dispersion strengthened austenitic stainless steel. The final forging temperature is not lower than 950℃, and the heat treatment includes solution treatment and aging. The solution treatment temperature is 1100~1200℃, and the aging temperature is 550~650℃. The composition, calculated by mass fraction of raw materials, includes 20.0–22.0 wt.% of Cr, 28.0–30.0 wt.% of Ni, 2.0–3.0 wt.% of Al, 1.0–2.0 wt.% of Mo, 0.6–1.0 wt.% of Nb, 0.1–0.4 wt.% of Zr, 0.05–0.15 wt.% of Y₂O₃, and 0.06–0.1 wt.% of C, with the balance being Fe.

2. The method of producing an oxide dispersion strengthened austenitic stainless steel according to claim 1, characterized by: Based on the mass fraction of the raw materials, the mass fraction of Cr is 21.0 wt.%; the mass fraction of Ni is 29.0 wt.%; the mass fraction of Al is 2.5 wt.%; the mass fraction of Mo is 1.5 wt.%; the mass fraction of Nb is 0.6 wt.%; the mass fraction of Zr is 0.2 wt.%; the mass fraction of Y2O3 is 0.08 wt.%; the mass fraction of C is 0.08 wt.%; and the balance is Fe.

3. A method of producing an oxide dispersion strengthened austenitic stainless steel according to any one of claims 1 or 2, c h a r a c t e r i z e d in that: The oxide dispersion strengthened austenitic stainless steel also has the following characteristics: (i) 14.26 to 14.72 mg dm of weight increase after 2000 h of corrosion in supercritical water at 550 °C / 25 MPa 2 ; (ii) 5.45 to 5.53 mg dm of weight increase in supercritical carbon dioxide at 550 °C / 25 MPa for 2000 h 2 ; (iii) The swelling rate of Fe ion irradiation at 550℃ for 50 dpa was 0.31~0.34%; (iiii) The elongation at 550℃ is 35.2~36.4%.

4. The preparation method according to claim 1, characterized in that: The refining temperature is 1470~1530℃, and the time is 8~12 minutes.

5. The preparation method according to claim 4, characterized in that: The Zr powder and Y2O3 powder are ball-milled under a high-purity argon atmosphere to obtain Zr-YO powder, wherein the mass ratio of Zr to Y elements is not less than 1.03; the mass fraction of anhydrous ethanol added during ball milling is 2.5% of the total mass of the powder; the ball-to-powder ratio is 5~10:1, the ball milling time is 25~50h, and the rotation speed is 200~400r / min.

6. The preparation method according to claim 4, characterized in that: The master alloy powder and Zr-YO powder are ball-milled and mixed under a high-purity argon atmosphere to obtain a mixed powder. The mass of Zr-YO powder is controlled so that the total Y2O3 content does not exceed 0.15%. The mass fraction of anhydrous ethanol added during ball milling is 2.5% of the total powder mass. The ball-to-powder ratio is 6~12:

1. The rotation speed is 150~300 r / min.

7. The preparation method according to claim 4, characterized in that: The mixture of powders is hot isostatically pressed and solidified, then forged and heat-treated to obtain the chemical dispersion strengthened austenitic stainless steel. The forging conditions are: initial forging temperature of 1100~1200℃ and total forging ratio of not less than 4:

1.

8. The preparation method according to claim 1, characterized in that: The heat treatment includes solution treatment and aging, wherein the holding time for solution treatment is 1-2 hours and the holding time for aging is 100-200 hours.

9. The application of oxide dispersion strengthened austenitic stainless steel prepared by any one of the preparation methods described in claims 1 to 8 in the cladding material of supercritical water / supercritical carbon dioxide cooled nuclear reactors.

Citation Information

Patent Citations

  • Austenite heat-resistance stainless steel forming Al2O3 protective layer spontaneously

    CN101906595A

  • Oxide-reinforced austenitic stainless steel and preparation method thereof

    CN113201681A